2020
DOI: 10.3390/w12010237
|View full text |Cite
|
Sign up to set email alerts
|

Lake Evolution, Hydrodynamic Outburst Flood Modeling and Sensitivity Analysis in the Central Himalaya: A Case Study

Abstract: Climate change has led to the formation of numerous high-altitude lakes of glacial origin in the Himalaya. Safed Lake is one of the largest glacial lakes, located at an elevation 4882 m a.s.l. in the state of Uttarakhand, central Himalaya, India. A temporal analysis of the lake surface using satellite imagery shows that the lake has grown more than double its size from 0.10 km2 to 0.23 km2 over the past 50 years. In this study, we performed a hazard assessment of the lake using 1D and 2D hydrodynamic modeling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Our modelling results in the Mo Chu basin in Bhutan revealed that channel roughness is not essential for the extent of the inundation, but plays an important role for the velocity and arrival time of the flood. These findings are in agreement with the results from other studies [23].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our modelling results in the Mo Chu basin in Bhutan revealed that channel roughness is not essential for the extent of the inundation, but plays an important role for the velocity and arrival time of the flood. These findings are in agreement with the results from other studies [23].…”
Section: Discussionsupporting
confidence: 94%
“…In version 3.0, voids are filled by using Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER), Global Digital Elevation Model 2 (GDEM2), USGS Global Multiresolution Terrain Elevation Data (GMTED) 2010, and USGS National Elevation Dataset (NED). SRTM elevation products are very common, freely available used in many GLOF studies [22,23].…”
Section: Digital Elevation Modelsmentioning
confidence: 99%
See 3 more Smart Citations